Constraining cavern backgrounds for the LUX-ZEPLIN experiment - Fearon, NM (2024)
There is an abundance of evidence, both astrophysical and cosmological, for the existence of non-luminous, gravitationally interacting matter that cannot be accounted for by the current Standard Model - dark matter. It is estimated that dark matter accounts for ~84% of the matter density of the Universe, but has yet to be directly detected.